Bioarcheology in the northwest Italy. Our experience - Larentis, Omar; Gorini, Ilaria (Medicina Historica, 2019)
In this letter we report our experience in the bioarchaeological field during the last 10 years. We would like to focus the attention on the importance of interdisciplinary approach, in order to better comprehend archaeological record and the history of our territory.